Post-thaw addition of pentoxifylline to equine semen previously cryopreserved with different concentrations of cholesterol-loaded cyclodextrin - Vilela, Virginia Maria Toledo; Gomes, Lorena Leticia Oliveira; Diniz, Juliana Horta Wilke; Miranda, Thayná Grazielle Rodrigues; Toyama, Bárbara Calefo; Silva, Deborah Freitas [UNESP]; Ladislau, Pedro Thomaz; Oliveira, Anna Julia; Ignácio, Fernanda Saules [UNESP]; Monteiro, Gabriel Augusto (Elsevier, 2023)
Cholesterol-loaded cyclodextrin (CLC) grants resistance to sperm during cryopreservation but may compromise sperm capacitation and fertility (Zahn et al. Theriogenology, 2002;58(2):237:240). Stimulants of sperm kinetics like pentoxifyllin (PTX) may increase sperm energy production and stimulate metabolic pathways responsible for sperm capacitation (Guasti et al. Anim.Reprod.Sci. 2017;179:27-34). The present study aimed to stimulate semen motility by adding PTX after thawing of semen previously cryopreserved with different concentrations of CLC. Mangalarga Marchador stallions (n=12; 4-14 years) were assigned to four groups: (G1) untreated control, (G2) inclusion of cholesterol-loaded cyclodextrin (CLC) at concentrations of 1mg, (G3) 1.5mg and (G4) 2mg. Two straws of each stallion per group were thawed and divided into two aliquots, pentoxifylline (2 mg/mL, 7.18 mM) homogenized in BotuCrio®, Botupharma, Brazil (PTX: G1, G2, G3 e G4) was added to one and not to other aliquot (No-PTX: G1, G2, G3 and G4). Sperm kinetics was analyzed by CASA (Sperm Class Analyzer, SCA® v.4.0 Microptic®) immediately after thawing (T0) or at 40 minutes (T40), 80 minutes (T80) and 120 minutes (T120) after thawing after incubation at 37°C. For statistical analysis, ANOVA F-test was performed.Intracellular hydrogen peroxide production was estimated by flow cytometry with dichlorodihydrofluorescein diacetate. Fertility was tested by deep horn insemination 0 to 6h after ovulation: No-PTX G1, No-PTX G3 and PTX G3. PTX reduced sperm velocity parameters at all times (p<0.05) compared to the groups without addition of pentoxifylline (No-PTX G1, G2, G3 and G4). Egg yolk based semen extenders may interfere with PTX cell penetration as they reduce permeability of the cell membrane. Regarding the integrity of the sperm plasma membrane and production of hydrogen peroxide, the use of pentoxifylline conferred an increase in sperm possibly under oxidative stress in the control group, with injured plasma membrane and with intracellular hydrogen peroxide (G1 PTX). When PTX was added to the group with highest concentration of cholesterol (G4 PTX), the intactness of the plasma membrane was improved, but with intracellular hydrogen peroxide. Mitochondrial potential and plasma membrane destabilization were also evaluated (n.s.). Pregnancy rates were 50% (2/4) for No-PTX G1, 67% (2/3) for No-PTX G3 and 67% (2/3) for PTX G3. In conclusion, addition of PTX did not interfere with mitochondrial potential, membrane destabilization and conception rate but was detrimental to cell longevity and to sperm kinetics.